Neonatal Morbidity After Management of Vaginal Noncephalic Second-Twin Delivery by Residents. Issue 6 (December 2018) - Schmitz, Thomas; Korb, Diane; Azria, Elie; Deruelle, Philippe; Kayem, Gilles; Rozenberg, Patrick; Sananès, Nicolas; Sénat, Marie-Victoire; Sentilhes, Loic; Vayssière, Christophe; Winer, Norbert; Goffinet, François
Abstract : OBJECTIVE: To assess neonatal mortality and morbidity according to whether a resident or senior obstetrician initially managed vaginal delivery of noncephalic second twins. METHODS: The JUmeaux MODe d'Accouchement study was a national, prospective, population-based, cohort study of twin deliveries in 176 maternity units in France, where active management of second-twin delivery is recommended. The primary outcome of our study was a composite of neonatal mortality and morbidity. Neonatal outcomes of noncephalic second twins born at or after 32 weeks of gestation after vaginal delivery of the first twin were compared according to the initial managing practitioner—supervised resident or senior obstetrician. Deliveries performed by a senior obstetrician after failure by a resident were classified as resident deliveries. Deliveries in maternity units without residents were excluded. We used multilevel multivariable Poisson regression models and propensity score matching to control for indication bias and potential confounders, including the maternity unit status. We performed subgroup analyses according to gestational age at delivery, before or after 37 weeks of gestation, and to the noncephalic second twin presentation, breech or transverse. RESULTS: Among 1, 376 noncephalic second-twin deliveries, 545 (39.6%) were initially managed by a resident and 831 (60.4%) by a senior obstetrician. Residents failed to deliver the second twin in 125 (22.9%) women. Composite neonatal mortality and morbidity did not differ between the resident and senior groups (13/545 [2.4%] vs 29/831 [3.5%]; adjusted relative risk 0.78, 95% CI 0.35–1.74). Subgroup analyses were consistent with the overall analysis. CONCLUSION: Supervised resident and senior staff management of noncephalic second-twin vaginal delivery is associated with similar neonatal morbidity and mortality, which supports continued training of residents in such deliveries. Abstract : Supervised resident and senior staff management of noncephalic second-twin vaginal delivery is associated with similar neonatal morbidity.